Estratégia para a regulação por fase de microrredes trifásicas ilhadas - Delgado, Thainá Matos Santana (2025)
Distributed generation, especially with renewable energy sources, has been rapidly gaining popularity, and with it, the need for studies to ensure quality in the supply of energy has been increasing. Therefore, microgrids emerge as an alternative for formatting a grid that foresees elements of distributed generation in its structure while allowing the combination of intelligence and security mechanisms, enabling energy supply in grid-connected or islanded mode. In the study of islanded microgrids, one of the main challenges is maintaining the balance between generation and load.With photovoltaic solar generation being the most popular distributed energy source today and the most common single-phase configuration in a scenario of generations close to the loads, it is essential to understand how these elements interact with each other and how they react to the constant intermittency existing in the system. In this regulatory scenario, one of the main problems is the load imbalance between the three phases of the islanded microgrid. In this work, phase regulation is proposed, that is, the supply with single-phase PV/BESS (Photovoltaic/Battery Energy Storage System) units to increase the operating capacity in all operating states of the microgrid. The system performance in the face of load imbalance is tested and compared with the operation of a three-phase unit instead of three per phase. The work developed through simulations in the Matlab/Simulink software and the microgrid with the three single-phase units proved effective in maintaining the voltage balance delivered to the loads. Despite not having control layers for this purpose, the system with single-phase units presented greater operational flexibility, proving a simple solution for operating in microgrids with a high degree of unbalance.